Differentiating methicillin resistant and susceptible Staphylococcus aureus from ocular infections using photoacoustic labeling - Edgar, Robert H.; Samson, Anie-Pier; Kowalski, Regis P.; Kellum, John A.; Hempel, John; Viator, John A.; Jhanji, Vishal (Frontiers in Medicine, 2023)
Introduction Antibiotic resistance in bacterial species constitutes a growing problem in the clinical management of infections. Not only does it limit therapeutic options, but application of ineffective antibiotics allows resistant species to progress prior to prescribing more effective treatment to patients. Methicillin resistance in Staphylococcus aureus is a major problem in clinical infections as it is the most common hospital acquired infection. Methods We developed a photoacoustic flow cytometer using engineered bacteriophage as probes for rapid determination of methicillin resistance in Staphylococcus aureus with thirteen clinical samples obtained from keratitis patients. This method irradiates cells under flow with 532 nm laser light and selectively generates acoustic waves in labeled bacterial cells, thus enabling detection and enumeration of them. Staphylococcus aureus isolates were classified from culture isolation as either methicillin resistant or susceptible using cefoxitin disk diffusion testing. The photoacoustic method enumerates bacterial cells before and after treatment with antibiotics. Decreasing counts of bacteria after treatment indicate susceptible strains. We quantified the bacterial cells in the treated and untreated samples. Results Using k-means clustering on the data, we achieved 100% concordance with the classification of Staphylococcus aureus resistance using culture. Discussion Photoacoustics can be used to differentiate methicillin resistant and susceptible strains of bacteria from ocular infections. This method may be generalized to other bacterial species using appropriate bacteriophages and testing for resistance using other antibiotics.